Determinants of Stigma Attitude Among People Living with HIV - Nursalam . (Journal of Global Pharma Technology, 2019)
Objective: Human immunodeficiency virus / acquired immunodeficiency syndrome (HIV/AIDS) is still a stigma in the community and becomes a barriers in dealing with HIV. This study aimed to identify the determinants of stigma attitude among people living with HIV/AIDS (PLWHA).Methods: This study used a cross-sectional design. Sample collection was carried out by simple random sampling involving 135 Housewife suffered by HIV in Surabaya. The independent variables were policy support, patient characteristics (including age, sex, education level, marital status, occupation, HIV status, first being diagnosed with HIV), family factors (including family burden and family resilience). The dependent variables were stigma. Data were collected using a questionnaire. The analysis used binary logistic regression with a significance level of p ≤0.05. Results: The results showed there are five factors related to stigma in PLWHA, namely policy support (p = 0.019), marital status (p = 0.039), first being diagnosed with HIV (p = 0.006), family burden (p = 0.000) and family resilience (p = 0.041). Out of five variables, only four had a significant effect on stigma, namely marital status (OR = 0.009; 95% CI 0.000 – 0.697), first being diagnosed with HIV (OR = 7,464; 95% CI 1,820 - 30,617), family burden (OR = 0.075; 95% CI 0,017 - 0.329), and family resilience (OR = 0.010; 95% CI 0.000 - 0.381).Conclusion: The determinants of stigma attitude among PLWHA include policy support, marital status, first being diagnosed with HIV, family burdens and family endurance. Tackling stigma on HIV which involves various sectors including society, family, private and government.Keywords: HIV/AIDS; PLWHA, Stigma attitude.